Evaluasi Pelaksanaan Pengelolaan PDAM Tirta Karimun Desa Lubuk Kabupaten Karimun - Setiawan, Ramadhani; Kurnianingsih, Fitri (Jurnal Ilmu Administrasi Negara (JUAN), 2018)
PDAM Tirta Karimun is a regional water supply company that provides services for estimating clean water for the community in Tanjung Batu Kundur. This study aims to see how the PDAM's servants are in providing services to the PDAM user community. This research was carried out descriptively with a qualitative approach, in this qualitative descriptive study the researcher will provide a systematic, factual and accurate description of the facts according to the scope of the research title. From the results of the research in this PDAM, this research resulted in the result that this PDAM has provided transparent and responsible services, but in this service there are still many shortcomings, especially in the water management and distribution, many problems such as not running water during the dry season, turbid water during the rainy season and where water is not suitable for consumption because it is muddy and smelly when after the rain, after the dry season and when the water is not mixed with chemicals. The conclusion in this study is that the PDAM service still has many shortcomings even though they have done what they have to do. For suggestions, it is expected to provide the expected service where the community is greatly helped if the PDAM runs smoothly, therefore it is expected to improve its quality and service.